Synthesis and Characterization of Pi-Conjugated Monomers for Coordination Polymers - Pivsa-Art, Sommai (Frontiers in Engineering Innovation Research, 2003)
(pi)-Conjugated monomers of substituted 1,4-phenylenediarnines and 1;’3-phenylenediarnines derivatives were synthesized and characterized with [superscript1] H NMR, [superscript13]C NMR, mass spectroscopy and elemental analysis. The corresponding coordination polymers were prepared by reactions of the monomers with transition salts in various conditions.